Legal and ethical values in the resolution of research-related disputes: how can IRBS respond to participant complaints? - Underhill, Kristen (Journal of empirical research on human research ethics : JERHRE, 2014)
Under US federal regulations, participants providing informed consent must receive information regarding whom to contact in case of a research-related injury or complaint. Although informed consent processes routinely direct participants to contact institutional review boards (IRBs) with questions or concerns, there has been little empirical study of the ways in which IRBs act to resolve participants' research-related complaints. This article explores available literature on participant complaints, considers the responsibilities of IRBs in dispute resolution, and outlines a research agenda. As a case study, this review considers disputes arising from HIV/AIDS research, focusing on novel issues arising from biomedical HIV prevention trials.
Keywords: Biomedical Research; Dissent and Disputes; Ethics Committees, Research; Ethics, Research; HIV Infections; Humans; Informed Consent; Questionnaires; Social Responsibility; United States